2017
DOI: 10.1016/j.scitotenv.2016.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biodiesel fuel on “real-world”, nonroad heavy duty diesel engine particulate matter emissions, composition and cytotoxicity

Abstract: Biodiesel is regarded by many as a "greener" alternative fuel to petroleum diesel with potentially lower health risk. However, recent studies examining biodiesel particulate matter (PM) characteristics and health effects are contradictive, and typically utilize PM generated by passenger car engines in laboratory settings. There is a critical need to analyze diesel and biodiesel PM generated in a "real-world" setting where heavy duty-diesel (HDD) engines and commercially purchased fuel are utilized. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 50 publications
1
20
2
Order By: Relevance
“…What is more noticeable, however, is that the addition of 20% of biodiesel in the fuel mixture resulted in a decrease of 25% in PAHs emissions in the particle-phase for SCR-off and 32% for SCR-on. Similar results were found by previous studies (Turrio-Baldassarri et al, 2004;He et al, 2010;He, 2016;Yilmaz and Davis, 2016;Martin et al, 2017), however without test the simultaneous effect of biodiesel blends and SCR aftertreatment system. Our results concur with the findings of He et al (2010), who compared several studies, concluding that, on average, a reduction of 23% in PAHs emissions can be expected with a 20% addition of biodiesel to the fuel.…”
Section: Particle-phase Pahssupporting
confidence: 91%
See 2 more Smart Citations
“…What is more noticeable, however, is that the addition of 20% of biodiesel in the fuel mixture resulted in a decrease of 25% in PAHs emissions in the particle-phase for SCR-off and 32% for SCR-on. Similar results were found by previous studies (Turrio-Baldassarri et al, 2004;He et al, 2010;He, 2016;Yilmaz and Davis, 2016;Martin et al, 2017), however without test the simultaneous effect of biodiesel blends and SCR aftertreatment system. Our results concur with the findings of He et al (2010), who compared several studies, concluding that, on average, a reduction of 23% in PAHs emissions can be expected with a 20% addition of biodiesel to the fuel.…”
Section: Particle-phase Pahssupporting
confidence: 91%
“…It seems therefore that only in the case of a combination of increased biodiesel additions and aftertreatment use, a reduction of Nitro-PAHs emissions was observed. This contrasts with Martin et al (2017) who found that B20 can reduce overall Nitro-PAHs concentrations in particle phase emissions in comparison to diesel, without aftertreatment.…”
Section: Particle-phase Nitro-pahscontrasting
confidence: 83%
See 1 more Smart Citation
“…Differences in fuel can have a significant effect on cdPM properties, including size distribution, surface area, ability to generate reactive oxygen species, and volatile content. [1013]…”
Section: Introductionmentioning
confidence: 99%
“…Chemically speaking, biodiesel is referred to lower methyl esters of long chain fatty acids, synthesized by transesterification with lower alcohols or by esterification of fatty acids. Partially due to its diversity in feedstocks of the production and scales of plant, however, biodiesel in nature has a wide spectrum in its fuel quality [8][9]. The parameters that define the quality of biodiesel can be divided into two groups.…”
Section: Introductionmentioning
confidence: 99%